New Model of Vegetation Monitoring Using Flying NIR Cameras with NDVI Parameters and C-means. (March 2019) - Ubaya, Huda; Sukemi,; Purnama Sari, Ayu
Abstract: Vegetation is an assemblage of the plant and various constituent flora collectively in a particular region. This research was conducted to test a new model in observing the level of vegetation by using a NIR camera that has an NRG filter, to obtain the NDVI value as the parameter in determining the level of vegetation in a region. The further stage was processing the NDVI value using contrast enhancement and Gaussian smoothing for image enhancement. The results obtained from this stage were clustered using c-means which produced 5 cluster values and the centroid value could be a reference to the value of vegetation in the desired region. Cluster with NDVI value range from - 1 to 0.09 showed the value for water and land while the value range above 0.09 showed the cluster for plants.